Maximizing Energy Efficiency: Harnessing Thermoelectric Power from Car Exhaust for Battery Recharge - Zarawi, Amirul Hakimi; Sym Sy Yi , (Evolution in Electrical and Electronic Engineering, 2024)
This research project explores the area of sustainable energy by exploring new ways of using waste heat to generate electricity. The focus is on using thermoelectric generator (TEGs) to capture the heat energy in the vehicle exhaust and convert it into electricity, which is stored in batteries. This approach incorporates information from an extensive literature review and uses previous findings to inform the design and manufacture of exhaust TEG systems. An important part of this research is to understand the relationship between the voltage generated by the TEG module and its distance from the heat source, which is car exhaust. This project investigates the output voltage change under different conditions, which provides valuable insight into the optimal TEG layout for better energy harvesting. In addition, the study examines exhaust gas temperatures from gasoline and diesel vehicles, showing the thermal characteristics of different types of engines. Tests for this purpose include the careful configuration of the TEG system, including components such as heat sinks, cooling blocks, and lithium batteries for energy storage. This study evaluates the time required for a lithium battery to charge to a certain level, which is relevant to the efficiency of energy storage systems. These results not only provide a better understanding of TEG applications but also provide insight into developing efficient and sustainable energy solutions. An important finding is that the closer the TEG is to the exhaust of the car, the higher the voltage it produces. Knowing this will help us design the best TEG system for each type of vehicle. Finally, we learned how long it takes to charge a lithium battery using the energy generated by the TEG. This will help us improve energy storage systems to achieve sustainable energy solutions. These findings will help us make better use of waste heat from the car exhaust to produce electricity.